Energi Biomassa sebagai Sumber Energi Terbarukan: Karakteristik Organic Solid Waste Biopellet (OSWBp) dari Limbah Padat Organik - Hardiansyah Tambunan; Dayun Ifanda; Sundari Marsudi; Hanna Tresia Silalahi; M. Rizki Rahmadan; Yoram Lefrand Halawa (Jurnal Sylva Scienteae, 2026)
Organic solid waste, which is abundant and easily available, has great potential to be used as raw material for biomass energy. This study aims to produce a source of biomass energy in the form of biopellets from a mixture of organic solid waste consisting of vegetable waste, durian peel, and sawdust. The study was conducted following systematic stages through preparation, pelletization, biopellet characterization, and data analysis. Next, to evaluate the effect of raw material type and mixing ratio with sawdust on the properties of biopellets, statistical analysis was performed using a Factorial Completely Randomized Design (FCRD). The results showed that the moisture content, density, ash content, and calorific value of the biopellets met the ISO 17225-6:2021 class B standard. Mixing vegetable and durian peel raw materials with wood powder can produce high-quality biopellets that meet international standards. Statistical analysis shows that the interaction between raw material types and mixing ratios with wood powder has a significant effect on the physical, mechanical, and chemical properties of biopellets. The results of this study indicate that organic solid waste has the potential to be developed as an alternative biopellet raw material that meets international quality standards and has the opportunity to be a sustainable renewable energy source.